ANALISIS PERMINTAAN RUMAH TANGGA TERHADAP AIR PDAM DI KELURAHAN KEDUNGDORO KOTA SURABAYA (JEB17 : Jurnal Ekonomi dan Bisnis, 2023)
This study aims to analyze whether the variables of PDAM water price, family income, number of family members, and use of well water affect PDAM water demand in Kedungdoro Village, Surabaya City. The total sample is 100 households selected using purposive sampling technique. Using multiple linear regression analysis with simultaneous tests, partial tests and, the coefficient of determination (R²). The results showed that PDAM water price, family income, and number of family members had a significant positive effect on PDAM water demand. Meanwhile, well water has no significant effect on PDAM water demand.